MIPs and Their Role in the Exchange of Metalloids - Jahn, Thomas P.; Bienert, Gerd P.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book is dedicated to the metalloids, a recently discovered group of substrates for a number of specific MIPs in a diverse spectrum of organisms. Particular focus is given to the essential boron, the beneficial silicon and the highly toxic arsenic. The respective MIP isoforms that facilitate the transport of these metalloids include members from several clades of the phylogenetic tree, suggesting that metalloid transport is an ancient function within this family of channel proteins.
Aquaporins: A Family of Highly Regulated Multifunctional Channels -- Phylogeny of Major Intrinsic Proteins -- Metalloids, Soil Chemistry and the Environment -- Arsenic Transport in Prokaryotes and Eukaryotic Microbes -- Metalloid Transport by Aquaglyceroporins: Consequences in the Treatment of Human Diseases -- Roles of Vertebrate Aquaglyceroporins in Arsenic Transport and Detoxification -- Molecular Mechanisms of Boron Transport in Plants: Involvement of Arabidopsis NIP5;1 and NIP6;1 -- Silicon Transporters in Higher Plants -- Major Intrinsic Proteins and Arsenic Transport in Plants: New Players and Their Potential Role -- Major Intrinsic Proteins in Biomimetic Membranes.
Keywords: Medicine; Biomedicine; Biomedicine general